2002
DOI: 10.2320/matertrans.43.2847
|View full text |Cite
|
Sign up to set email alerts
|

Undercooled Melt Formation by Melting of Metastable Eutectic Structure in Al<SUB>2</SUB>O<SUB>3</SUB>-Y<SUB>2</SUB>O<SUB>3</SUB>-ZrO<SUB>2</SUB> System

Abstract: This paper presents a selection of the eutectic systems in the Al 2 O 3 -Y 2 O 3 -ZrO 2 pseudo-ternary system and the production of the undercooled melt due to melting of the metastable eutectic structure at the metastable eutectic temperature. In the pseudo-ternary system, there are two eutectic systems; one is the Al 2 O 3 -YAG(Y 3 Al 5 O 12 )-ZrO 2 equilibrium system and the other is the Al 2 O 3 -YAP(YAlO 3 )-ZrO 2 metastable system. The eutectic system was selected by maximum melt temperature before solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The selection of the eutectic systems in the present study was consistent with the previous work. 21) Nucleation temperature tended to decrease with increasing cooling rate. As the cooling rate increases, the rate of the heat release increased.…”
Section: Morphological Transition In the Almentioning
confidence: 99%
See 4 more Smart Citations
“…The selection of the eutectic systems in the present study was consistent with the previous work. 21) Nucleation temperature tended to decrease with increasing cooling rate. As the cooling rate increases, the rate of the heat release increased.…”
Section: Morphological Transition In the Almentioning
confidence: 99%
“…X-ray diffraction patterns of the solidified specimens indicated that the specimens consisted of the metastable eutectic system. According to the previous work, 21) heating the melt up to 2 300 K inhibited the YAG nucleation and the melt was undercooled below the metastable eutectic temperature. The solidification below the metastable eutectic temperature obeyed the metastable eutectic path.…”
Section: Morphological Transition In the Almentioning
confidence: 99%
See 3 more Smart Citations